Reconhecimento e trabalho em Axel Honneth: os trabalhadores offshore na Bacia de Campos – Brasil - Adelia Maria Miglievich Ribeiro; Valter Luis Fernandes de Sales (Confluenze, 2010)
Honneth brings the Hegel from the Jena period into debate and revisits the subject of the struggle for recognition. More recently, he re-examines Durkheim who, eighty years after Hegel, insists on a new form of economy which is not dissociable from ethics. Honneth propounds that capitalism, besides pursuing economic efficiency goals, will need to remodel itself rooted in the normative criteria which can ensure it as a social integration strength. Honneth elects distressful experiences at work as an evidence that outrage is able to trigger the struggles for recognition, which may be politically articulated or not. This research elects offshore workers in Brazil and demonstrates to what extent does a tiptop economic sector also promote recognition asymmetries among its workers, especially when its productive goals antagonize the demands for dignity.